The Role of Neurolinguistics for Language and Speech Disorders - Gusdi Sastra; Mohamad Saiful Haq; Handoko Handoko (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
This paper explains the significance of neurolinguistics as one of interdisciplinary fields of linguistics encompassing the analytical procedures on individual speech disorders in producing and using language. The result of analysis is used for designing a model and strategy to improve their language capacity.Â Neurolinguistics roadmap covers some previous researches done by Sastra et all since 2006. Those studies investigate language and speech disorders including thinking ailments, and answer the inherent question on neurolinguistics contribution for addressing the individual problems to express themselves. Those problems are caused by some disorders on the left and right hemispheres of the brain. Science wise, neurolinguistics will always develop because the language phenomena always happen in human life through thinking and speech.